Calcium-calmodulin kinase II and cytoplasmic polyadenylation element-binding protein 1 pair as a biological swtich in long-term memory. - Lee, Qian Qian. (2011)
Personal identification numbers, directions to the office and mother’s birthday. These are just three amongst billions of others that we can recall with ease. The human brain, with its finite physical size and limited number of nerve cells, seem to have an exceedingly incredible capability to learn new things and store gargantuan amounts of information. However, beneath the surface of this remarkable organ lies an intricate and highly interconnected network of neurons fuelled by an array of specialised neurotransmitters.